Non-antibiotics disrupt colonization resistance against enteropathogens - Anne Grießhammer; Jacobo de la Cuesta-Zuluaga; Patrick Müller; Cordula Gekeler; Jan Homolak; Hsuan Chang; Katharina Schmitt; Chiara Planker; Verena Schmidtchen; Suchira Gallage; Erwin Bohn; Taylor H. Nguyen; et al. (Nature, 2025)
Abstract Non-antibiotic drugs can alter the composition of the gut microbiome1, but they have largely unknown implications for human health2. Here we examined how non-antibiotics affect the ability of gut commensals to resist colonization by enteropathogens3. We also developed an in vitro assay to assess enteropathogen growth in drug-perturbed microbial communities. Pathogenic Gammaproteobacteria were more resistant to non-antibiotics than commensals and their post-treatment expansion was potentiated. For 28% of the 53 drugs tested, the growth of Salmonella enterica subsp. enterica serovar Typhimurium. (S. Tm) in synthetic and human stool-derived communities was increased, and similar effects were observed for other enteropathogens. Non-antibiotics promoted pathogen proliferation by inhibiting the growth of commensals, altering microbial interactions and enhancing the ability of S. Tm to exploit metabolic niches. Drugs that promoted pathogen expansion in vitro increased the intestinal S. Tm load in mice. For the antihistamine terfenadine, drug-induced disruption of colonization resistance accelerated disease onset and increased inflammation caused by S. Tm. Our findings identify non-antibiotics as previously overlooked risk factors that may contribute to the development of enteric infections.